COVID-19 and Health Sector Development Plans in Africa: The Impact on Maternal and Child Health Outcomes in Uganda - Atim MG; Kajogoo VD; Amare D; Said B; Geleta M; Muchie Y; Tesfahunei HA; Assefa DG; Manyazewal T (Dove Medical Press, 2021)
Mary Gorret Atim,1,2 Violet Dismas Kajogoo,1,3 Demeke Amare,1,4 Bibie Said,1,5 Melka Geleta,1,6 Yilkal Muchie,1,7 Hanna Amanuel Tesfahunei,1,8 Dawit Getachew Assefa,1,9 Tsegahun Manyazewal1 1Center for Innovative Drug Development and Therapeutic Trials for Africa (CDT-Africa), College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Public Health, Busitema University Faculty of Health Sciences, Mbale, Uganda; 3Mafie District Hospital, Mafia Island, Pwani Region, Tanzania; 4Ethiopian Food and Drug Administration Authority (EFDA), Addis Ababa, Ethiopia; 5Kibong'oto National Tuberculosis Hospital, Kilimanjaro, Tanzania; 6Federal Ministry of Health, Addis Ababa, Ethiopia; 7All Africa Leprosy and Rehabilitation Training (ALERT) Centre, Addis Ababa, Ethiopia; 8Hager Biomedical Research Institute, Asmara, Eritrea; 9Department of Nursing, College of Medical and Health Sciences, Dilla University, Dilla, EthiopiaCorrespondence: Mary Gorret AtimCenter for Innovative Drug Development and Therapeutic Trials for Africa (CDT-Africa), College of Health Sciences, Addis Ababa University, P.O. Box 9086, Addis Ababa, EthiopiaEmail atimgoretti@gmail.comIntroduction: Health Sector Development Plans (HSDPs) aim to accelerate movement towards achieving sustainable development goals for health, reducing inequalities, and ending poverty. Reproductive, maternal, newborn and child health (RMNCH) services are vulnerable to economic imbalances, including health insecurity, unmet need for healthcare, and low health expenditure. The same vulnerability influences the potential of a country to combat global outbreaks such as the COVID-19. We aimed to provide some important insights into the impacts of COVID-19 on RMNCH indicators and outcomes of the HSDP in Uganda.Methods: We conducted a descriptive study of secondary data obtained from the Ugandan government-led portals, supplemented by analyses of relevant articles published up to 06 May 2021 and deposited in PubMed.Results: Through synthesizing actionable and relevant evidence, we realized that RMNCH in Uganda is highly affected by the COVID-19 pandemic and the lockdown measures. The impact was across immunization, antenatal, sexual and reproductive health, emergency and obstetric, and postnatal care services. There was a decline sharply by 9.6% for under-five vitamin A coverage, 9% for DPT3HibHeb3 coverage, 6.8% for measles vaccination coverage, 6% for isoniazid preventive therapy coverage, and 3% for facility-based deliveries. Maternal and under-five deaths increased by 7.6% and 4%, respectively. Outreaches were rarely conducted in the lockdown period.Conclusion: The COVID-19 pandemic has created a multitude of questions regarding the optimal policies to mitigate the disease while minimizing the unintended detrimental consequences of RMNCH. The lockdown restrictions threatened to reverse the progress made on the national HSDP for RMNCH. In Uganda, where young women are vulnerable to early marriage, unintended pregnancies, and unsafe abortion, access to RMNCH services should continue regardless of the COVID-19 status in the country. We urge that Uganda and other African countries should build resilient and sustainable health systems that can withstand emerging diseases like the COVID-19.Keywords: COVID-19, reproductive, maternal, newborn and child health, Health Sector Development Plan, Africa, Uganda